2020
DOI: 10.15407/ubj92.06.126
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative/antioxidant balance and matrix metalloproteinases level in the knee cartilage of rats under experimental osteoarthritis and probiotic administration

Abstract: The aim of this work was to investigate the effect of the poly-strain probiotic on oxidative-antioxidant balance and the level of matrix metalloproteinases (MMPs) in rat knee cartilage under experimental osteoarthritis. Osteoarthritis was induced by a single injection of monoiodoacetate into the knee joint of rats. Probiotic was administered daily for 14 days. Knee cartilages homogenate was used to evaluate the content of reactive oxygen species (superoxide anion and hydrogen peroxide), products of lipids pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Previous studies [28] showed that in the serum and cartilage tissue of rats with experimental joint pathology the content of superoxide radical and hydrogen peroxide, lipid peroxidation products and proteins increased, and the functioning of the antioxidant system was impaired.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies [28] showed that in the serum and cartilage tissue of rats with experimental joint pathology the content of superoxide radical and hydrogen peroxide, lipid peroxidation products and proteins increased, and the functioning of the antioxidant system was impaired.…”
mentioning
confidence: 97%
“…Due to the wide range of biological activity, they promote to the production of mediators which have a positive effect not only on the functions of the gastrointestinal tract, but also on metabolic processes in the organism. The introduction of PB in animals with experimental joints pathology restored the disturbed oxidative-antioxidant balance both in the joint (locally) and at the systemic level (in the blood), reduced the intensity of inflammation in the organism, prevented the activation of proteolytic enzymes and the catabolism of collagen proteins, suppressed destructive processes in the tissues of the joint [28,30].…”
mentioning
confidence: 99%